A safe and robust dual-network hydrogel electrolyte coupled with multi-heteroatom doped carbon nanosheets for flexible quasi-solid-state zinc ion hybrid supercapacitors. Issue 37 (14th September 2021) - Wu, Dandan; Ji, Chenchen; Mi, Hongyu; Guo, Fengjiao; Cui, Haonan; Qiu, Pengtao; Yang, Nianjun
Abstract : A κ-CG/PAAm/Zn(CF3 SO3 )2 hydrogel electrolyte was constructed, which displays high ionic conductivity and satisfactory mechanical properties. The quasi-solid-state ZHSC based on ACNS and the as-designed hydrogel shows excellent cycling stability and a superior energy density. Abstract : Aqueous zinc ion hybrid supercapacitors (ZHSCs) are receiving increasing research interest because of their superiority in safety, economy, and high water compatibility. However, the corrosion problems coupled with dendrite growth in an aqueous system severely limit the potential use of zinc storage systems with long service life. To delicately address the above obstacles, a κ-carrageenan/polyacrylamide/Zn(CF3 SO3 )2 hydrogel electrolyte (denoted as κ-CG/PAAm/Zn(CF3 SO3 )2 ) with an ionically and covalently double crosslinked network was constructed, which possesses a high ionic conductivity of 2.3 S m −1, a high tensile strength of 34.6 kPa with a superior stretchability of 599.0%, and an excellent compression strength of 75.3 kPa at 75.0% strain. The double crosslinked polymer chains realize uniform zinc deposition. In addition, the intrinsic hydrophilic groups in the κ-carrageenan (κ-CG) and polyacrylamide (PAAm) chains can well immobilize water molecules, which favor electrolyte ion transport. Moreover, nitrogen and sulphur co-doped carbon nanosheets (denoted as ACNS) characterized by the rich amorphous phase associated with lots of short-range ordered microcrystalline regions were prepared as the cathode material in this work, which exhibits a high capacity of 116.4 mA h g −1 coupled with superior rate performance and long-term cycling stability (108.0% capacity retention over 10 000 cycles) for an aqueous Zn//ACNS ZHSC. A quasi-solid-state ZHSC based on ACNS and κ-CG/PAAm/Zn(CF3 SO3 )2 exhibits a specific capacity of 100.5 mA h g −1 at 0.25 A g −1 with a high capacity retention of 50.8% at 20 A g −1 . The as-fabricated ZHSC also shows excellent cycling stability of 10 000 cycles as well as a superior energy density of 86.5 W h kg −1 at a power density of 215.3 W kg −1 . The ZHSC can also be used as a reliable source to drive various kinds of electronics ( e.g., mobile phones and electronic timers), which uncovers a feasible strategy for engineering the high-performance hydrogel electrolytes and cathode materials for ZHSC applications.